Correction: Single nanosheet can sustainably generate oxygen and inhibit respiration simultaneously in cancer cells. Issue 2 (11th January 2021) - Huang, Wei-Qiang; Wang, Fei; Shen, Ai-Zong; Zhang, Lei; Nie, Xuan; Zhang, Ze; Chen, Guang; Xia, Lei; Wang, Long-Hai; Ding, Sheng-Gang; Meng, Qing-Yong; Zhang, Wen-Jian; et al.
Abstract : Correction for 'Single nanosheet can sustainably generate oxygen and inhibit respiration simultaneously in cancer cells' by Wei-Qiang Huang et al., Mater. Horiz., 2021, DOI: ; 10.1039/d0mh01446j .